Perceived impact of the COVID-19 pandemic on entertainment events in Malaysia - Ismail, Khairiah; Abdul Razak, Dhiya Hikmahana; Ng, Wai Yee; Abdullah, Nawal Hanim (Taylor and Francis, 2023)
The purpose of this paper is to examine the impact of COVID-19 on Malaysian entertainment events by examining the risk assessments, responses and control measures taken by event organisers. Utilising a qualitative method, in-depth interviews were conducted with seven informants—organisers who actively organised entertainment events before the COVID-19 pandemic. From the coding analysis using the Atlas.ti software, four major themes emerged: event cancellation and postponement, financial loss, unemployment and unsatisfactory virtual events. However, there is a limitation in the context of previous literature, especially in the creative industry. The findings are relevant to event managers, who can use the insights as a reference for their business growth and consolidation.